Pencegahan Bullying di Yayasan Intaniyah Desa Sadangmekar Tinjauan dari Perspektif Pendidikan dan Psikologis - Carnelian, Tiara Putri (PROCEEDINGS UIN SUNAN GUNUNG DJATI BANDUNG, 2024)
This article discusses the role of KKN (Community Service Program) in Sadangmekar Village in fostering social awareness and addressing the bullying behavior faced by students at the Al-Intaniyyah Foundation or MI-MTS Al-Intaniyyah. The KKN activities in this village aim primarily to empower the local community, especially through teaching programs, via various activities such as empowering children, providing outreach on mental health issues, and educating about the dangers of bullying. This article reviews the positive impact achieved by the Community Service Program in Sadangmekar Village in building social awareness among students, motivating them to be more enthusiastic and passionate about education, and helping them face contemporary challenges, particularly the phenomenon of bullying. With a focus on this effort, this article provides insights into how local approaches such as Community Service (KKN) can be an important instrument in developing social understanding and addressing the current issues faced by students in their respective environments.